Penyuluhan Iliotibial Band Syndrome (ITBS) pada Komunitas Sukoharjo Runners - Zannuba Alifah Chafsoh; Kintan Candra Surya Paramita; Rizqy Febriansyah (Universitas 45 Surabaya, 2022)
Iliotibial Band Syndrome (ITBS) is generally considered an injury to runners. Iliotibial Band Syndrome (ITBS) is one of the most common overuse injuries of the lower extremities. ITBS is the occurrence of inflammation due to friction between the iliotibial band and the underlying tissue structure, this is due to repetitive flexion and extension movements or overuse during activities such as running and cycling. This activity aims to increase the understanding of ITBS to runners in order to minimize the occurrence of injuries and to treat ITBS injuries. This activity focuses on providing education and counseling about ITBS injuries, the material presented includes definitions, etiology, symptoms, prevention, and management of ITBS injuries. Evaluation by being given a questionnaire before and after the delivery of the material. Based on the results of the evaluation carried out by the participants, it was found that many participants were able to answer the questions correctly, it can be concluded that the participants had understood the material regarding ITBS injuries.